88.5k views
20 votes
Solving exponential equation 10^3 = 10^2x + ^ 3

1 Answer

6 votes

Answer:

x = 4

Explanation:

Simplifying

2x + -10 = 10 + -3x

Reorder the terms:

-10 + 2x = 10 + -3x

Solving

-10 + 2x = 10 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.

-10 + 2x + 3x = 10 + -3x + 3x

Combine like terms: 2x + 3x = 5x

-10 + 5x = 10 + -3x + 3x

Combine like terms: -3x + 3x = 0

-10 + 5x = 10 + 0

-10 + 5x = 10

Add '10' to each side of the equation.

-10 + 10 + 5x = 10 + 10

Combine like terms: -10 + 10 = 0

0 + 5x = 10 + 10

5x = 10 + 10

Combine like terms: 10 + 10 = 20

5x = 20

Divide each side by '5'.

x = 4

Simplifying

x = 4

User Nicolas Charvoz
by
5.2k points